Atypical GATA protein TRPS1 plays indispensable roles in mouse two-cell embryo. Issue 4 (16th February 2019) - Liu, Yue; Xu, Songhua; Lian, Xiuli; Su, Yang; Zhong, Yuhuan; Lv, Ruimin; Mo, Kaien; Zhu, Huimin; Xiaojiang, Wang; Xu, Lixuan; Wang, Shie
ABSTRACT: Zygotic genome activation (ZGA) is one of the most critical events at the beginning of mammalian preimplantation embryo development (PED). The mechanisms underlying mouse ZGA remain unclear although it has been widely studied. In the present study, we identified that tricho-rhino-phalangeal syndrome 1 (TRPS1), an atypical GATA family member, is an important factor for ZGA in mouse PED. We found that the Trps1 mRNA level peaked at the one-cell stage while TRPS1 protein did so at the two/four-cell stage. Knockdown of Trps1 by the microinjection of Trps1 siRNA reduced the developmental rate of mouse preimplantation embryos by approximately 30%, and increased the expression of ZGA marker genes MuERV-L and Zscan4d via suppressing the expression of major histone markers H3K4me3 and H3K27me3. Furthermore, Trps1 knockdown decreased the expression of Sox2 but increased Oct4 expression. We conclude that TRPS1 may be indispensable for zygotic genome activation during mouse PED.